Interleukin-1 Receptor Antagonist And Their Roles In Different Diseases (Journal of Pharmaceutical Negative Results, 2023)
The interleukin 1 receptor antagonist (IL1Ra) family of molecules now includes one secreted isoform (sIL1Ra) and three intracellular isoforms (icIL1Ra1, 2, and 3). Extensive evidence indicates that the sole biological function of sIL1Ra seems to be to competitively inhibit IL1 binding to cell-surface receptors. Although intracellular IL1Ra1 may be released from keratinocytes under some conditions, the intracellular isoforms of IL1Ra may carry out additional as yet poorly defined roles inside cells. Maintenance of a balance between IL1 and IL1Ra is important in preventing the development or progression of inflammatory disease in certain organs. Both the secreted and intracellular isoforms of IL1Ra contribute to maintenance of this balance. An allelic polymorphism in intron 2 of the IL1Ra gene (IL1RN*2) predisposes to the development or severity of a variety of human diseases largely of epithelial cell origin. Both the impaired production of IL1Ra and the overproduction of IL1â are related to the presence of this allele. Restoration of the balance between IL1Ra and IL1 through a variety of approaches is a therapeutic goal in specific chronic inflammatory diseases.